Logic behind the continuous growth across the s-curve - A method for the structured construction of a business growth flywheel model - Dong, Bo (Decision Making: Applications in Management and Engineering, 2023)
Based on Amazon’s successful business experience, the flywheel effect has proven to be an effective method for guiding companies across the S-curve. More scholars have investigated the flywheel model of business growth, which uses the flywheel effect to help companies achieve leapfrogging growth. More research is needed to determine whether the structured business growth model is universally applicable to different industries and stages of enterprise development. According to this study, in the VUCA era, businesses are forced to accelerate their transformation due to rapid changes in the competitive environment. A more agile approach to growth model optimization is required there. As a result, this study takes a traditional theory approach, and this research builds a flywheel model of enterprise growth on the original flywheel effect theory. The three-step method of producing the corporate growth flywheel model proposed in this study is validated by the empirical results of the case study, and the universality and operability of the structured business growth flywheel model are verified by the case study of the leading real estate intermediary company, Lianjia.